Performance modification of third-order optical nonlinearity of chalcogenide glasses by nanocrystallization. Issue 15 (15th October 2019) - Yang, Yinwei; Sun, Tingting; Lin, Changgui; Dai, Shixun; Zhang, Xianghua; Ji, Wei; Chen, Feifei
Abstract: We demonstrate the modification of the third-order optical nonlinearity (TONL) of chalcogenide glasses (within the GeS2 –In2 S3 –CsCl ternary system) by nanocrystallization, i.e., by controlling the precipitation of nanocrystals (in pure In2 S3 phase) within the amorphous background. Compared with the parent glass, the resultant chalcogenide glass ceramics (ChGCs) have unchanged infrared transmittance but modifiable optical bandgap energy with treatment duration. Both nonlinear refraction coefficient and nonlinear absorption coefficient of the ChGCs are increased due to the appearance of In2 S3 nanocrystals. ChGCs subjected to heat treatment for 1.3–2 h are found to exhibit the optimum TONL performance.